Solid‐Supported Synthesis and 5‐HT7/5‐HT1A Receptor Affinity of Arylpiperazinylbutyl Derivatives of 4, 5‐dihydro‐1, 2, 4‐triazine‐6‐(1H)‐one. (6th March 2015) - Grychowska, Katarzyna; Masurier, Nicolas; Verdié, Pascal; Satała, Grzegorz; Bojarski, Andrzej J.; Martinez, Jean; Pawłowski, Maciej; Subra, Gilles; Zajdel, Paweł
<x xml:space="preserve">Abstract</x> A series of arylpiperazinylbutyl derivatives of 4, 5‐dihydro‐1, 2, 4‐triazine‐6(1H)‐ones was designed and synthesized according to the new solid‐supported methodology. In this approach, triazinone scaffold was constructed from the Fmoc‐protected glycine. The library representatives showed different levels of affinity for 5‐HT7 and 5‐HT1A receptors; compounds 13, 14 and 18–20 were classified as dual 5‐HT7/5‐HT1A receptors ligands. The structure–affinity relationship analysis revealed that the receptor affinity and selectivity of the tested compounds depended on the kind of substituent in position 3 of triazinone fragment as well as substitution pattern of the phenylpiperazine moiety.